2021
DOI: 10.1590/fst.30520
|View full text |Cite
|
Sign up to set email alerts
|

Acer triflorum: A maple species that serves as a resource for nervonic acid and that has an ultralow erucic acid content

Abstract: In this experiment, pulse NMR and gas chromatography were used to determine the seed oil content and fatty acid composition of Acer triflorum. In addition, the morphological characteristics of samaras and seeds were measured by conventional methods. The results showed that the average oil content of the tested seeds was 33.44 ± 0.098% and revealed the presence of 16 fatty acids, of which six constituted 93.57% of the total oil cocent: linoleic acid, oleic acid, docosadienoic acid, peanutenedioic acid, palmitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As an excellent color-leaf ornamental tree species, it is used for landscaping projects, especially for the corridor forest landscape [3,4]. In addition, A. triflorum is beneficial to ecological protection of saline-alkali zones due to its strong cold tolerance and salt-alkali resistance [5]. Due to the ornamental characteristics and gardening application, researchers have studied the morphological and physiological traits suitable for developing propagation methods [6] and seed contents in A. triflorum [7]; however, relatively little is known about molecular mechanism of leaf color change.…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent color-leaf ornamental tree species, it is used for landscaping projects, especially for the corridor forest landscape [3,4]. In addition, A. triflorum is beneficial to ecological protection of saline-alkali zones due to its strong cold tolerance and salt-alkali resistance [5]. Due to the ornamental characteristics and gardening application, researchers have studied the morphological and physiological traits suitable for developing propagation methods [6] and seed contents in A. triflorum [7]; however, relatively little is known about molecular mechanism of leaf color change.…”
Section: Introductionmentioning
confidence: 99%
“…Their seed oil is reported of high importance regarding its yield and composition (He at al. 2021, Qian et al 2017, Qiao et al 2017, Qiao et al 2018, Su et al 2021. For example, Hovanet et al (2015) reported that Acer platanoides L. and Acer pseudoplatanus L. seed oil yield varies respectively between 3.3 to 4.89 % and 5.12 to 6.97 %.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting fatty acid mentioned by the authors is the gamma-linolenic acid, found in lower rates (3.3 % and 2.5 % of the two seed oils respectively), and has several health benefits regarding cardiovascular and skin diseases. Another interesting fatty acid found in some maple species is nervonic acid which has an important role in brain health by helping regenerate nerve fibres and increasing the capacity of neurodevelopment (Su et al 2021). He et al (2021) reported that nervonic acid was found in 46 Chinese maple species seed oil varying from 2.84 % for Acer cappadocicum to 13.9 % for Acer elegantulum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation